Fate of Calanus spp. reproduction and development under different environmental stressors - Eide, Helene Overaa (UiT Norges arktiske universitet, 2016)
The large calanoid copepods Calanus glacialis and C. ﬁnmarchicus is a key link between primary producers and higher trophic levels in Arctic marine ecosystems being used as indicator species of respective Arctic and Atlantic water. In this study, the egg production successand population development of Calanus glacialis and C. finmarchicus were studied in Isfjorden, Svalbard, from February to August 2016. An experimental study, investigating potential effects of different oil spill clean-up methods on C. glacialis reproduction was also conducted to study the fate of Calanus spp, under different environmental stressors. The two Calanus species had similarly large populations in Isfjorden in winter and entered the surface water simultaneously in late winter-spring. Their reproductive strategy diﬀered althoughs. C. glacialis started to produce eggs earlier than C. finmarchicus and had a clear egg production maximum at the peak of the spring bloom that dropped to a minimum soon after the bloom. . C. ﬁnmarchicus had a a modest, stable egg production over a relatively long time span from early May to July. The late spawned eggs, however, did not make it, resulting in lower recruitment of C. finmarchicus than C. glacialis in Isfjorden in 2016. Transformed Atlantic water prevailed in Isfjorden in 2016 and there were no strong evidence of major advective events from February to August. The increase in population numbers in June was thus mainly due to local recruitment, which also the timing of the egg production and the surface temperatures supported. C. glacialis timed its reproduction and population development more successfully than C. finmarchicus to the prevailing abiotic and biotic environment in Isfjorden. By the end of August, C. glacialis had reached its main overwintering stage and was already concentrated at depth. In comparison, C. finmarchicus had a biomodal vertical distribution end of August with still high numbers of young developmental stages in the surface. In the oil exposure experiment dispersant, ...